2017
DOI: 10.1017/s1431927617000605
|View full text |Cite
|
Sign up to set email alerts
|

Focused Ion Beam Preparation of Specimens for Micro-Electro-Mechanical System-based Transmission Electron Microscopy Heating Experiments

Abstract: Micro-electro-mechanical systems (MEMS)-based heating holders offer exceptional control of temperature and heating/cooling rates for transmission electron microscopy experiments. The use of such devices is relatively straightforward for nano-particulate samples, but the preparation of specimens from bulk samples by focused ion beam (FIB) milling presents significant challenges. These include: poor mechanical integrity and site selectivity of the specimen, ion beam damage to the specimen and/or MEMS device duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…[47] With the development of high temperature-resistant materials, the working temperature could reach more than 1500°C. [48][49][50] Recently, Pérez et al reported a newly-designed micro-heating system with ultra temporal-stability, which kept the heating sample at constant z-position (no bulging) up to 700°C and allowed EDX acquisition in the TEM up to 1000°C. [16,51] With the help of precision machining technology and MEMS technology, a special holder equipped with a nanoreactor can be manufactured for in-situ TEM study, which allows gases to be introduced and sealed within the reactor (illustrated in Figure 2c).…”
Section: Specimen Holdermentioning
confidence: 99%
“…[47] With the development of high temperature-resistant materials, the working temperature could reach more than 1500°C. [48][49][50] Recently, Pérez et al reported a newly-designed micro-heating system with ultra temporal-stability, which kept the heating sample at constant z-position (no bulging) up to 700°C and allowed EDX acquisition in the TEM up to 1000°C. [16,51] With the help of precision machining technology and MEMS technology, a special holder equipped with a nanoreactor can be manufactured for in-situ TEM study, which allows gases to be introduced and sealed within the reactor (illustrated in Figure 2c).…”
Section: Specimen Holdermentioning
confidence: 99%
“…In recent years, as the use of microelectromechanical systems (MEMS)-based chips for in situ TEM experiments increases, the preparation of specimens becomes even more challenging. One of the most widely used methods is to fabricate thin lamellae via focused ion beam (FIB) (Duchamp et al, 2014;Mele et al 2016;Vijayan et al 2017). This method has the advantage of being able to fabricate a specimen with a uniform thickness and the entire specimen preparation is completed only within the FIB.…”
Section: Introductionmentioning
confidence: 99%
“…However, the supporting lm in the chip may be torn or the surface of specimen may be damaged during FIB milling. Also, lift-out for positioning the lamella on MEMS chips performed inside the FIB (e.g., in-situ lift-out (INLO)) requires multiple and complex manipulation and an special inclined stage that minimizes the ion ux experienced by the chip during FIB milling (Duchamp et al, 2014;Vijayan et al 2017;Pivak et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, FIB has been widely used to fabricate specimens for transmission electron microscopy (TEM). In particular, FIB sampling method becomes more important in micro-electromechanical system (MEMS)-based in situ TEM (Mele et al 2016;Vijayan et al 2017) in which we can observe real-time microstructural changes influenced by external stimuli such as electrical current and thermal and mechanical stress. For in situ TEM with electrical MEMS chips, the formation of a conducting path with low electrical resistance is required to connect TEM specimens to the electrodes in a MEMS chip.…”
Section: Introductionmentioning
confidence: 99%